Efeito do método de lotação sobre a carga parasitária em ovinos e a contaminação do pasto por larvas de estrongilídeos - Troncha, Paula Mara Ribeiro (2019)
Sheep production faces a variety of health challenges, including gastrointestinal parasitosis, mainly caused by Haemonchus contortus, hematophagous nematode, pathogenic, hard control, and which causes severe losses in herds. The pasture management practices allow the reduction of contamination of the environment with infective stages. Thus, the objective of this study was to evaluate the effect of the stocking method on loading of parasites and the contamination of Brachiaria brizantha cv. Marandu / Urochloa brizantha cv. Marandu by infective larvae during the rainy season in the Cerrado region. The experiment was carried out in the Small Ruminant Sector of Capim Branco Experimental Farm, Federal University of Uberlandia, from February to April 2017 and from March to May 2018. A randomized block design was used with two treatments, continuous (LC) and intermittent (LI), and nine subjects per block and treatment in 12 paddocks. The variables evaluated in sheep were body mass (MC), body condition score (ECC), fecal egg counts (FEC), FAMACHA© System. To evaluate the dynamics of pasture contamination, there was evaluated the number of infective larvae (L3) and average L3 per kg of dry matter (L3/MS) by means of pasture collections both pre and post grazing of each area managed in LI; and once every 21 days on areas maintained under LC. There were no statistical differences (p> 0.05) for MC, ECC, as well as for loading parasites and L3 grass contamination between the LI and LC treatments during the two years of experiment. In the coproparasitological examinations were found Strongylid, Strongyloides spp., Moniezia spp. eggs as well as Eimeria spp. oocysts. The most prevalent genus detected in coproculture were Haemonchus spp. with 68.5% in LC and 87.5% in LI, and Trichostrongylus spp. in the LC and LI groups, with 31% and 12%, respectively. The recovery of L3 / g MS was higher in pasture under LC than in that managed in LI during the third cycle of 2017. The continuous or intermittent stocking method did not influenced on the parasitosis level in pregnant sheep such as in the contamination of the grass by infective larvae.